Factors Associated with Academic Performance Including Socioeconomic Level: a Multiple Regression Study of University Students - Garbanzo Vargas, Guiselle María (2014)
The author systematically performed a quantitative research study of the factors associated with academic performance from a socioeconomic point of view in students from Universidad de Costa Rica. Using multiple regression models, the author analyzed factors associated with the academic performance of students awarded the highest level of scholarship because of their socioeconomic status and students not applying for a scholarship because they are enrolled in majors with high or low demand at Universidad de Costa Rica. This paper provides an explanatory framework on the subject, as well as inputs for the management of public higher education. One of the main findings indicates that academic performance is a multicausal and highly complex phenomenon. The paper also highlights the main institutional, pedagogical, and psychosocial factors associated with academic performance, taking into account the socioeconomic component.